Removal of Chromium(VI) from Electroplating Effluent by Leaves of Cauliflower - Farooqui, Mazahar; Kotharkar, Sandeep (Asian Journal of Chemistry, 2010)
The paper described the use of leaves of cauliflower for the removal of Cr(VI) from industrial waste stream. The dried and powdered raw materials were used for the removal of waste water. It is observed that at room temperatute leaves of cauliflower show maximum adsorption property. As the pH increases the adsorption property decreases of the effluent